2015
DOI: 10.1016/j.devcel.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ciliary Phosphoinositide Content Regulates Trafficking and Sonic Hedgehog Signaling Output

Abstract: Ciliary transport is required for ciliogenesis, signal transduction, and trafficking of receptors to the primary cilium. Mutations in inositol polyphosphate 5-phosphatase E (INPP5E) have been associated with ciliary dysfunction; however, its role in regulating ciliary phosphoinositides is unknown. Here we report that in neural stem cells, phosphatidylinositol 4-phosphate (PI4P) is found in high levels in cilia whereas phosphatidylinositol (4,5)-bisphosphate (PI(4,5)P2) is not detectable. Upon INPP5E inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
343
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(360 citation statements)
references
References 56 publications
15
343
2
Order By: Relevance
“…2 G and H); however, the basally high cAMP level in cilia depends on adenylyl cyclase 5/6 activity that requires PIP 3 but not stimulatory G proteins. Others have reported that PI(4,5)P 2 and INPP5E play critical roles in ciliary signaling (31) and that inhibition of PI3K prevents IGF-I-stimulated Akt and SHH-mediated increase in Gli activity in a luciferase assay (32). Additionally, cross-talk between inhibition of HH and PI3K expression was also reported in some medulloblastomas (33).…”
Section: Discussionmentioning
confidence: 95%
“…2 G and H); however, the basally high cAMP level in cilia depends on adenylyl cyclase 5/6 activity that requires PIP 3 but not stimulatory G proteins. Others have reported that PI(4,5)P 2 and INPP5E play critical roles in ciliary signaling (31) and that inhibition of PI3K prevents IGF-I-stimulated Akt and SHH-mediated increase in Gli activity in a luciferase assay (32). Additionally, cross-talk between inhibition of HH and PI3K expression was also reported in some medulloblastomas (33).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, two recent studies 8,9 specifically addressed PIP composition within the PC. While one study used PI-specific …”
Section: Phosphoinositides In the Primary Ciliummentioning
confidence: 99%
“…28 The lack of PI(4,5)P 2 regulation inside the cilia is expected to result in aberrant signaling, in part due to abnormal GPCRs levels. 8 The concentration of PI(4,5)P 2 is controlled by both 5′ kinases and phosphatases. 7 However, besides immunofluorescence-based detection of PIP5Kγ at the ciliary base, 8 no information is available concerning the localization and function of PIP5 kinases in the PC.…”
Section: What Is Known In Terms Of Pip Functional Relevance?mentioning
confidence: 99%
See 2 more Smart Citations